A study on customer retention (repeat purchase) at Peladang Mart Sdn. Bhd. / Amirah Salwani Shabani - Shabani, Amirah Salwani (2012)
The purpose of this research is to examine the relationship between the price, trust and satisfaction for the change of customer retention. The study was conducted on customers Peladang Mart Sdn. Bhd. the different cultural background. The sample size ranged from 125 customers at Alor Star, Kedah Darul Aman. Respondents are asked to evaluate the price, trust and satisfaction for change through questionnaires printed in English and Malay. Various data analysis methods used to analyze data such as frequency analysis, reliability analysis, Pearson correlation analysis and multiple regression analysis. Overall, price, trust and satisfaction showed an intermediate effect on customer retention.